A qualitative investigation of the psychosocial services utilised by care-givers of patients with Alzheimer’s disease and related dementias in southwestern Uganda - Abaasa, Catherine; Obua, Celestino; Wakida, Edith K.; Rukundo, Godfrey Zari (Ageing & Society, 2021)
Individuals with Alzheimer’s disease and related dementias often require substantial support from other people. Much of the care-giving is from family members who eventually experience physical, emotional and financial stress, depression and fatigue. In Uganda, families are a cornerstone in providing care to individuals with dementia. However, little is known about the psychosocial supports available to the care-givers in their care-giving role. We assessed the psychosocial supports available to care-givers of individuals with Alzheimer’s disease and related dementias in southwestern Uganda. We conducted 34 in-depth interviews at three referral hospitals at which care-givers identified by the treating clinicians were approached for informed consent. The interviews were conducted until thematic saturation was reached, and the interviews were translated and transcribed. Thematic content analysis was used to analyse the data. Care-giver supports were structured into two major themes: medical supports utilized and supports beyond the medical care system. Medical supports highlighted information provided by medical professionals. Supports beyond the medical care system included emotional and instrumental supports provided by religious leaders, the local communities and family members. Care-givers for individuals with dementia in southwestern Uganda receive educational support from medical practitioners, and unstructured emotional and instrumental supports from the family and community.
Keywords: Alzheimer’s disease; Dementia; low- and middle-income countries (LMICs); Psychosocial support; Care-giver